Global service platforms in local markets: case taxi services - Jukka Heikkilä; Marikka Heikkilä (Slovenia, 2022)
In this paper we discuss digital platform economy and use theory of Governance of Commons by Elinor Ostrom as a lens through which we look at related problems and social issues, such as tragedy of the commons. We discuss how communities can react to side effects and overgrazing of free, common resources by norms and rules. We illustrate the issue with the opening of taxi service markets to new entrants such as Uber.
32nd Bled eConference: Humanizing Technology for a Sustainable Society